Wyzysk w perspektywie sprawiedliwości - Stoiński, Andrzej (Annales. Etyka w Życiu Gospodarczym, 2014)
The paper refers to selected problems of exploitation in the face of justice. The analysis is based on the definitions of exploitation contained in the Polish Penal and Civil Codes. The main subject of our interest is the identification of the necessary and sufficient conditions for the recognition of exploitation as being unjust. Supplementary question will refer to a specific type of justice which should be considered in this case. In respect to this we should consider retributive, distributive and social justice. Another important factor in this regard is the accepted theory of value. In the considered subject we will focus on the labour theory of value. The principal problem could be reduced to questions whether the exploitation is ipso facto unjust and how these two phenomena are related to each other.